Vasoactive intestinal peptide, whose receptor‐mediated signalling may be defective in alopecia areata, provides protection from hair follicle immune privilege collapse. (9th August 2016) - Bertolini, M.; Pretzlaff, M.; Sulk, M.; Bähr, M.; Gherardini, J.; Uchida, Y.; Reibelt, M.; Kinori, M.; Rossi, A.; Bíró, T.; Paus, R.
Summary: Background: Alopecia areata (AA) is an autoimmune disorder whose pathogenesis involves the collapse of the relative immune privilege (IP) of the hair follicle (HF). Given that vasoactive intestinal peptide (VIP) is an immunoinhibitory neuropeptide released by perifollicular sensory nerve fibres, which play a role in IP maintenance, it may modulate human HF‐IP and thus be therapeutically relevant for AA. Objectives: To answer the following questions: Do human HFs express VIP receptors, and does their stimulation protect from or restore experimentally induced HF‐IP collapse? Is VIP signalling defective in AA HFs? Methods: Firstly, VIP and VIP receptor (VPAC1, VPAC2) expression in human scalp HFs and AA skin was assessed. In HF organ culture, we then explored whether VIP treatment can restore and/or protect from interferon‐γ‐induced HF‐IP collapse, assessing the expression of the key IP markers by quantitative (immuno‐)histomorphometry. Results: Here we provide the first evidence that VIP receptors are expressed in the epithelium of healthy human HFs at the gene and protein level. Furthermore, VIP receptor protein expression, but not VIP + nerve fibres, is significantly downregulated in lesional hair bulbs of patients with AA, suggesting defects in VIP receptor‐mediated signalling. Moreover, we show that VIP protects the HF from experimentally induced IP collapse in vitro, but does not fully restore it once collapsed. Conclusions: These pilot data suggest that insufficient VIP receptor‐mediated signalling may contribute to impairing HF‐IP in patients with AA, and that VIP is a promising candidate 'HF‐IP guardian' that may be therapeutically exploited to inhibit the progression of AA lesions. Abstract : What's already known about this topic? Alopecia areata pathogenesis involves the collapse of hair follicle (HF) immune privilege. Vasoactive intestinal peptide (VIP) is an immunoinhibitory neuropeptide released by perifollicular nerve fibres fundamental for immune homeostasis. What does this study add? VIP receptors are expressed in human HFs. Alopecia areata hair bulbs present defects in VIP receptor expression but not in VIP + nerve fibre density. VIP administration prevents and partially restores experimentally induced HF immune privilege collapse. What is the translational message? VIP and its analogues may be used in alopecia areata management. VIP and its analogues may reduce the progression and spreading of alopecic foci in alopecia areata. The most promising therapeutic approach may be a combination therapy, which aims first to upregulate the expression of VIP receptors on the cell surface and subsequently to activate these receptors with appropriate agonists. Linked Comment: Porter and Tobin. Br J Dermatol 2016;175 :460 .